Implementasi N-Modular Redundancy with spare pada Sistem Penyiraman Otomatis - Sultan Achmad Chidir Fajar; Rakhmadhany Primananda; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Automatic watering are system that controlled by using type of code so that watering can be happen without human interference. In this case watering has an important role to help humans in caring for plants so that plants can grow properly, as well as the system sometimes can be failed this can make plants unable to grow properly. This failure can be reduced by implementing a fault tolerant system with hardware redundancy techniques in which the use of hardware redundancy makes a system have additional modules to minimize system failures. N-modular with spare is a hardware redundancy technique, This technique makes a system have a spare module where this module works to minimize system failure. In this system the microcontroller retrieves data from the capacitive soil moisture sensor using I2C, the data is forwarded to the voter. Voters will do majority voting where the voting results will be forwarded to the Disagreement Detector. The disagreement detector has the role of turning off the spare module, the active module and turning on the spare module. The module is deactivated when the data retrieved by the module does not match the other modules. The system can keep running as long as the module does not exceed the error limit of the system design. From the research, the system has successfully run according to the wishes of the testers and the system has been able to perform fault masking, detection and location and recovery. When the system was added using the n-modular with spare system, the reliability increased by 5.72% from 92.7% to 98.42%.